2022
DOI: 10.1155/2022/4691576
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Distance Measurement and System Pharmacology Approach Uncover the Novel Protective Effects of Biotransformed Ginsenoside C-Mc against UVB-Irradiated Photoaging

Abstract: Long-term exposure to ultraviolet light induces photoaging and may eventually increase the risk of skin carcinogenesis. Rare minor ginsenosides isolating from traditional medicine Panax (ginseng) have shown biomedical efficacy as antioxidation and antiphotodamage agents. However, due to the difficulty of component extraction and wide variety of ginsenoside, the identification of active antiphotoaging ginsenoside remains a huge challenge. In this study, we proposed a novel in silico approach to identify potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Ginsenosides, triterpene saponins, are major bioactive compounds responsible for pharmacological activities of Panax (ginseng), which has traditionally been used to treat and prevent various conditions associated with aging including skin aging. Previous studies demonstrated that the rare minor ginsenosides (C-Mc and Mx), which may act as potential antiphotoaging compounds, suppressed MMP production via regulating MAPK/AP-1/NF-κB pathway and promoted collagen production via the TGF-β/Smad pathway in association with upregulation of Nrf2 signaling in UVB-irradiated human dermal fibroblasts ( Liu et al, 2018 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides, triterpene saponins, are major bioactive compounds responsible for pharmacological activities of Panax (ginseng), which has traditionally been used to treat and prevent various conditions associated with aging including skin aging. Previous studies demonstrated that the rare minor ginsenosides (C-Mc and Mx), which may act as potential antiphotoaging compounds, suppressed MMP production via regulating MAPK/AP-1/NF-κB pathway and promoted collagen production via the TGF-β/Smad pathway in association with upregulation of Nrf2 signaling in UVB-irradiated human dermal fibroblasts ( Liu et al, 2018 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and inflammation have a close interaction that leads to the progression of photoaging under UVR exposure. Oxidative stress is involved in collagen degradation in the skin, and inflammation stimulates epidermal thickening and reduces collagen contents in the epidermis and dermis [1,5,7,22,[59][60][61][62]. The MAPK family of kinases are major regulators involved in cell apoptosis and inflammatory responses that trigger the phosphorylation of c-Fos, c-Jun, and JunD proteins (AP-1 complex), leading to collagen degradation via upregulation of MMP-1, -3, and -9 [1,[5][6][7]54,55,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is involved in collagen degradation in the skin, and inflammation stimulates epidermal thickening and reduces collagen contents in the epidermis and dermis [1,5,7,22,[59][60][61][62]. The MAPK family of kinases are major regulators involved in cell apoptosis and inflammatory responses that trigger the phosphorylation of c-Fos, c-Jun, and JunD proteins (AP-1 complex), leading to collagen degradation via upregulation of MMP-1, -3, and -9 [1,[5][6][7]54,55,[59][60][61][62]. Activation of specific MAPK inhibitors, such as JNK and P38/MAPK, by blocking the Smad 3/4 complex has been suggested to suppress TGF-β expression, thereby impairing collagen syn-thesis [5,11,[59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…p21 and p53 are anti-oncogenes that promote cell senescence ( Chen Q. et al, 2020 ), and are also regarded as markers of skin aging. In fact, measurements of SOD activity, MDA/HYP levels, and Mmp-1/p21/p53 expression have been widely performed to assess aging and to screen anti-aging agents ( Sharpless, 2015 ; Lee et al, 2016 ; Sun et al, 2018 ; Li et al, 2022 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%